Framing Land Governance Issues in Indigenous and Settler Media within Canada - Harding, Robert; Ray, Sterling (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
This comparative study examines how the framing of Indigenous land governance issues—such as resource extraction activities on Indigenous territory and treaty negotiation—in Indigenous media differs from that in corporate news. Methods of Critical Discourse Analysis were applied to 66 news texts published in 2018 in large corporate newspapers, such as the National Post, and small Indigenous news outlets, such as Eagle Feather News. Researchers found that Indigenous media connected land governance issues to contemporary issues, such as racism and control over child welfare, as well as historical colonialism and Indigenous-Settler relations, while corporate news generally excluded any discussion of these contextual factors. While the main news frame in the Indigenous press was Indigenous people were not consulted, the dominant frame in corporate news was Indigenous peoples have already been adequately consulted. Corporate news discourse valorized Indigenous traditional territory solely based on its presumed “economic value.” By contrast, Indigenous publications offered a counternarrative, one that positioned land and the rest of the natural environment as something that has absolute value, and as indivisible from all living things, including people.